Hubungan Penggunaan Obat Golongan Statin terhadap GDS pada Pasien Diabetes Melitus Tipe 2 di Instalasi Rawat Inap Rsup Dr. M. Djamil Padang - Primadhini, Tessa Amanda; A, Almahdy; Arriva, Dzaskia (LPPM Universitas Dharma Andalas, 2026)
Dyslipidemia is one of the risk factors for cardiovascular disease in patients with type 2 diabetes mellitus, so statin therapy is often used to lower lipid levels and prevent cardiovascular complications. Although statins have clear benefits in the management of dyslipidemia, their effect on fasting blood glucose (FBG) levels still needs to be studied. This study aimed to determine the relationship between statin use and FBG levels in patients with type 2 diabetes mellitus. This study used a quantitative descriptive design with a retrospective approach. Data were obtained from the medical records of 82 patients with type 2 diabetes mellitus and dyslipidemia who were treated at the inpatient facility of Dr. M. Djamil Hospital in Padang. All patients in this study received statin therapy. The most commonly used statin was atorvastatin, which was used by 96.3% of patients, while simvastatin was used by 3.7% of patients. The results showed that the average decrease in random blood sugar levels in patients using atorvastatin was 55.65 mg/dL, while in patients using simvastatin it was 84.75 mg/dL. Although there was a numerical difference in the reduction of fasting blood glucose levels between the two statin groups, the difference found was not clinically significant. Thus, this study indicates that the use of statin drugs does not have a significant association with changes in fasting blood glucose levels in patients with type 2 diabetes mellitus.